A Comparative Analysis on Translation Strategies in the Bahasa Indonesia and Toba Bataknese Christian Hymns - Rafita Tioria Sianipar; Meisuri Meisuri; I Wayan Dirgayasa Tangkas; Winda Setiasari; Semaria Eva Elita Girsang (Institut Agama Kristen Negeri Tarutung, 2023)
This paper aims to examine and compare the translation strategies employed in the translation of originally written in English hymns into Indonesian and Toba Batak languages, and to identify commonalities and disparities in translation approaches, by using Peter Low’s (2005; 2013; 2017) strategy of song translation, i.e the translation, adaptation, and replacement. The data consists of a collection of hymns in English and their respective translations in Indonesian and Toba Bataknese. The results of data analyis discovered that adaptation was the most frequently used strategy in both Indonesian and Toba Batak translations. In addition, replacement strategy applied in the two target languages was also notable. The findings further indicate a consistent translation choice of the term